1998
DOI: 10.1016/s0893-133x(97)00168-1
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Dose-Dependent Global and Regional Cocaine-Induced Reductions in Brain Blood Flow Using a Novel Approach to Quantitative Single Photon Emission Computerized Tomography

Abstract: Ischemic stroke is a common cause of morbidity and mortality in cocaine addicts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Using specific examples for selected drugs, a large bolus of cocaine (0.5 mg/kg) decreases CBF in human basal ganglia by 20–30% (Wallace et al, 1996, Johnson et al, 1998), and a similar dose decreases cerebral blood volume (CBV) in the basal ganglia of non-human primates by 10–15% (Mandeville et al, 2011), values which are concordant with the human data when using the commonly applied power-law relationship between CBF and CBV (Grubb et al, 1973). In rodent models, even very large doses of psycho-stimulants produce changes in CBV that rarely exceed 20% in magnitude (Jenkins, 2012).…”
Section: Data Acquisitionsupporting
confidence: 57%
“…Using specific examples for selected drugs, a large bolus of cocaine (0.5 mg/kg) decreases CBF in human basal ganglia by 20–30% (Wallace et al, 1996, Johnson et al, 1998), and a similar dose decreases cerebral blood volume (CBV) in the basal ganglia of non-human primates by 10–15% (Mandeville et al, 2011), values which are concordant with the human data when using the commonly applied power-law relationship between CBF and CBV (Grubb et al, 1973). In rodent models, even very large doses of psycho-stimulants produce changes in CBV that rarely exceed 20% in magnitude (Jenkins, 2012).…”
Section: Data Acquisitionsupporting
confidence: 57%
“…Johnson et al, using novel quantitative single photon emission CT method for measuring brain blood flow, demonstrated that intravenous cocaine use is associated with a global reduction in brain blood flow. However, the reduction in blood flow was more pronounced in the dopamine-rich regions of the brain such as prefrontal, frontal, temporal and subcortical gray matter [ 17 ]. We hypothesize that posterior inferior cerebellar artery, posterior cerebral arteries, and lenticulostriate arteries are selectively prone to transient vasospasm due to the high adrenergic state from increased circulating catecholamines affecting their autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the mechanism of cocaine-related TIA and stroke are not completely understood, it is generally accepted that cocaine-induced vasoconstriction is a key contributing factor [2]. The effects of cocaine in various brain regions differ, not only because it causes increases in dopamine release and metabolism [3], but also due to cocaine-induced cerebral vasospasm, which appears to be most prominent in frontal cortical regions including prefrontal cortex and somatosensory cortex [4], where cerebral blood flow is most affected [5, 6]. Indeed, using contrast-enhanced ultrahigh-resolution optical coherence tomography, we recently showed that single or repeated cocaine administration to the mouse somatosensory cortex induced cerebral micro-ischemia [7].…”
Section: Introductionmentioning
confidence: 99%